2015
DOI: 10.1051/0004-6361/201527127
|View full text |Cite
|
Sign up to set email alerts
|

Light curves of the latest FUor: Indication of a close binary

Abstract: We monitored the recent FUor 2MASS J06593158-0405277 (V960 Mon) since November 2009 at various observatories and multiple wavelengths. After the outburst by nearly 2.9 mag in r around September 2014 the brightness gently fades until April 2015 by nearly 1 mag in U and 0.5 mag in z. Thereafter the brightness at λ > 5000 Å was constant until June 2015 while the shortest wavelengths (U, B) indicate a new rise, similar to that seen for the FUor V2493 Cyg (HBC722). Our near-infrared (NIR) monitoring between Decembe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…V960 Mon went into outburst in 2014 and shows all the necessary spectral properties of a bona fide FUor (Kóspál et al 2015 andreferences therein, Connelley &Reipurth 2018). Based on periodic oscillations in the outburst light curve, Hackstein et al (2015) suggests that it is a close binary. Kóspál et al (2015) studied the SED of the progenitor and found that it indicates the presence of a moderately flared disk and an outer envelope in the system, whose total mass is between 0.1-0.7 M , if we scale it to the new Gaia distance of 1574 pc from the previously assumed 450 pc.…”
Section: V960 Monmentioning
confidence: 99%
“…V960 Mon went into outburst in 2014 and shows all the necessary spectral properties of a bona fide FUor (Kóspál et al 2015 andreferences therein, Connelley &Reipurth 2018). Based on periodic oscillations in the outburst light curve, Hackstein et al (2015) suggests that it is a close binary. Kóspál et al (2015) studied the SED of the progenitor and found that it indicates the presence of a moderately flared disk and an outer envelope in the system, whose total mass is between 0.1-0.7 M , if we scale it to the new Gaia distance of 1574 pc from the previously assumed 450 pc.…”
Section: V960 Monmentioning
confidence: 99%
“…Results of photometric observations were presented in several studies. According to the result of Hackstein et al (2015), the maximum magnitude of V960 Mon was observed on 2014 October 6, which was 10.8 and 10.2 mag in the Sloan r-and i-bands, respectively. The brightness of V960 Mon gradually decreased by 0.5 -1 mag in the optical wavelength between 2014 October and 2015 April.…”
Section: Introductionmentioning
confidence: 96%
“…The information of brightness variation of V960 Mon during the period when the high-resolution spectra were observed is vital for understanding its spectroscopic variations. The brightness of V960 Mon in the r-and i-bands in 2014 October were 2.9 mag brighter than those in the quiescent phase (Hackstein et al 2015). The light curve of V960 Mon during the period when the spectra were collected was created with data of the American Association of Variable Star Observers (AAVSO).…”
Section: Brightness Variationmentioning
confidence: 99%
“…The maximum magnitude was ∼3 mag brighter in the optical wavelength compared to the quiescent phase. V960 Mon gradually faded by 0.5-1 mag between October 2014 and April 2015 (Hackstein et al 2015), and it kept fading with a lower rate. Spectroscopic observations of V960 Mon in the early phase of the outburst demonstrated typical characteristics of FUors.…”
Section: Introductionmentioning
confidence: 98%